The Effect of Increasing Valine, Isoleucine, and Tryptophan:Lysine Ratios on Pigs’ Growth Performance and Carcass Characteristics When Fed Diets with Increased Levels of Dietary Leucine:Lysine - Hadley R. Williams; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Chad W. Hastad; Zach B. Post (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 4,076 pigs (initially 86.5 ± 1.24 lb) were used across 2 experiments to evaluate the effect of increasing ratios of Val, Ile, and Trp to Lys on pig growth performance and carcass characteristics in corn-soybean meal-DDGS-based diets containing increased levels of dietary Leu:Lys. In both experiments, the 4 dietary treatments were as follows: 1) high soybean meal and low feed grade amino acids (control); 2) low soybean meal and high feed grade amino acids, with Val:Lys, Ile:Lys, and Trp:Lys at 67, 55, and 18, respectively, (low ratio); 3) same as diet 2 except Val:Lys, Ile:Lys, and Trp:Lys increased to 72, 60, and 21, respectively, (medium ratio); and 4) same as diet 2 except Val:Lys, Ile:Lys, and Trp:Lys increased to 80, 65, and 23, respectively (high ratio). All diets contained 30% DDGS until pigs reached approximately 220 lb, and then 20% DDGS until trial completion. Overall ADG and average ADFI increased (AA ratio; linear,P<0.05) as Val, Ile, and Trp ratios increased from low to high. Pigs fed the control diet exhibited increased ADG when compared to pigs fed low ratio diets, while pigs fed medium and high ratio diets showed intermediate performance. In summary, the soybean meal level can be reduced, and synthetic amino acid levels increased in high DDGS diets as long as ratios of Val, Ile, and Trp to Lys are increased.
Keywords: branch chain amino acids; finishing pigs; growth performance